MR imaging of optic pathways in patients with neurofibromatosis. - Brown, E W; Riccardi, V M; Mawad, M; Handel, S; Goldman, A; Bryan, R N (American Journal of Neuroradiology, 1987)
Twenty-one patients with documented neurofibromatosis had MR examinations to evaluate possible intracranial disease. In five cases the indication was a known or suspected optic glioma. Two patients were examined because of a history of seizures; the rest were examined as part of a baseline evaluation. Eighteen patients showed evidence of signal hyperintensity on T2-weighted images. Lesions involved the optic nerves, optic chiasm, optic tracts, lateral geniculate body, optic radiations, basal ganglia, periventricular white matter, cerebellar white matter, and dentate nucleus of the cerebellum. Comparison between MR and concurrent CT scans showed MR to be superior in demonstrating the posterior extent of optic-pathway gliomas. In addition, MR showed focal areas of hyperintensity in the basal ganglia, internal capsule, cerebellum, and/or white matter that were not detected on CT. Although we found MR to be superior to CT in detecting intracranial tumors in patients with neurofibromatosis, and in evaluating the extensive involvement of known lesions, the full clinical implications of our findings remain to be determined.